Addendum: Professional and elite young soccer players: Differences in functional movement screen™ values - Italo Sannicandro; Giacomo Cofano; Rosario D'Onofrio; Andrea Piccinno (Physical Education and Sports: Studies and Research, 2025)
This addendum provides additional statements on data availability and AI disclosure to enhance transparency and align the original article with current international publication standards. These updates do not affect the results, interpretation, or conclusions of the original publication.